Analysis of stunting handling indicators based on SSGI 2022 data in Lampung Province: Multilevel analysis - Betania, Sakha Ukta; Wiboworini, Budiyanti; Qadrijati, Isna (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: The implementation of specific and sensitive nutrition interventions is an effort to prevent the increasing prevalence of stunting in Indonesia. However, not all target indicators performed optimally in their implementation, which could affect the increase in stunting prevalence.Objectives: Analyze the dominant factors of stunting incidence among toddlers aged 12-13 months from suboptimal handling of stunting in Lampung Province.Methods: This study utilized a cross-sectional design with secondary data from the 2022 Indonesian Nutrition Status Survey. The variables in this study were iron tablet consumption, exclusive breastfeeding, growth monitoring, primary immunization, access to drinking water, access to sanitation, and the incidence of stunting, and considering heterogeneity in subdisctrict and regencies/municipalities. The subjects were 1.929 toddlers aged 12-23 months, selected by purposive sampling. Data were analyzed with a frequency distribution table, a Chi-Square test, and a multilevel binary logistic regression test.Results: Chi-square test showed there was no relationship between iron tablet consumption (p=0.362; OR=1.14), exclusive breastfeeding (p=0.164; OR=0.85), growth monitoring (p=0.807; OR=1.08), and access to sanitation (p=0.431; OR=1.18) with incidence of stunting. However, there was a relationship between primary immunization (p=0.008; OR=1.39) and acces to drinking water (p=0.023; OR=1.35). Multilevel test results showed that there was no effect of non-exclusive breastfeeding (aOR=0,84; p>0,05) not routine growth monitoring (aOR=1,03;p>0,05), inappropriate iron tablet consumption (aOR=1,14; p>0,05), inadequate access to sanitation (aOR=1,10; p>0,05), rural domicile (aOR = 1,03; p>0,05), number of community health centers (aOR=1,00; p>0,05) contour of mountain territory (aOR=0,89; p>0,05), and contour of water territory (aOR=0,83; p>0,05) with incidence of stunting. Household-level variation had the largest effect on stunting incidence, with an ICC of 7,63%.Conclusions: Incomplete primary immunization and inadequate access to drinking water were the dominant factors affecting stunting in toddlers aged 12-23 months in Lampung Province.